177k views
2 votes
If f(x)= 4x+3 and g(x)= 3x evalute f(x). g(x) for x=-1 over 2

User Tewe
by
4.3k points

1 Answer

7 votes

\bf \begin{cases} f(x)=4x+3\\ g(x)=3x\\ ------------\\ f(x)\cdot g(x)=(4x+3)(3x)\\ \qquad \qquad \qquad 12x^2+9x \end{cases} \\\\\\ \boxed{x=-\cfrac{1}{2}}\qquad \qquad 12\left( -(1)/(2) \right)^2+9\left( -(1)/(2) \right)\implies 12\left( -(1)/(2) \right)\left( -(1)/(2) \right)+9\left( -(1)/(2) \right) \\\\\\ 12\left( \cfrac{1}{4} \right)-\cfrac{9}{2}\implies 3-\cfrac{9}{2}\implies \cfrac{6-9}{2}\implies \cfrac{-3}{2}\implies -1(1)/(2)
User Ryk
by
4.4k points